Modulating emotion processing using transcranial alternating current stimulation (tACS) - A sham-controlled study in healthy human participants - Hu, Pengchong; He, Yuchen; Liu, Xiaoya; Ren, Zhengyu; Liu, Shuang (2021 43rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2021)
As an emerging non-invasive neuromodulation technique, transcranial alternating current stimulation(tACS) has been reported to be used in mood regulation, cognitive modulation and brain trauma recovery by applying specific frequency currents. However, the neuromodulatory mechanisms and effects of tACS on emotion processing are unclear. In this study, a single-blind experiment with 44 healthy subjects in 1:1 randomized groups (experimental group given 10 Hz-tACS and control group given sham-stimulation) was conducted. The effects of tACS applied to the prefrontal lobe on the brain's emotional state and emotional cognitive processing in response to emotional stimulation patterns were explored by designing two experimental paradigms of an 8-minute open and closed eye resting task and an emotional face oddball task. Power spectrum and event-related potentials were extracted to explore the effect of tACS on brain rhythm modulation and attention modulation. It was found that the experimental group showed significantly enhanced alpha rhythm in the whole brain range after tACS, especially in the parieto-occipital lobe. The rate of misclassification of neutral emotions into negative emotions was significantly lower and the amplitude of P2 and P3 of event-related potentials were significantly higher when performing the emotional face task after tACS, while the control group did not have this phenomenon. These results suggest that tACS can modulate and enhance alpha rhythm activity by synchronizing alpha oscillations in the frontoparietal attention network, thereby improving subjects' negative emotion cognitive bias and enhancing their emotion processing by increasing early and late levels of emotional attention.